2021
DOI: 10.1111/1365-2656.13618
|View full text |Cite
|
Sign up to set email alerts
|

Population level consequences of facultatively cooperative behaviour in a stochastic environment

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 115 publications
2
4
1
Order By: Relevance
“…Whilst we found no effect of helping experience on dominant breeding position acquisition, we did find that helpers became dominant breeders later in life than those that did not help. This result is consistent with previous studies on female Seychelles warblers (Busana et al, 2022) and the lance-tailed manakin (Duval et al 2013). If individuals spend time helping prior to gaining a dominant breeding position, it follows that they become a dominant breeder at an older age compared to individuals that did not help and, instead, acquired dominance at their earliest opportunity.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Whilst we found no effect of helping experience on dominant breeding position acquisition, we did find that helpers became dominant breeders later in life than those that did not help. This result is consistent with previous studies on female Seychelles warblers (Busana et al, 2022) and the lance-tailed manakin (Duval et al 2013). If individuals spend time helping prior to gaining a dominant breeding position, it follows that they become a dominant breeder at an older age compared to individuals that did not help and, instead, acquired dominance at their earliest opportunity.…”
Section: Discussionsupporting
confidence: 92%
“…We found that experience as a helper had no effect on whether an individual acquired a dominant breeding position in either males or females. At first sight, this finding conflicts with a previous study on the Seychelles warbler, which found that female helpers were less likely to acquire a dominant breeding position than female non-helpers (Busana et al, 2022). However, Busana et al…”
Section: Discussioncontrasting
confidence: 65%
See 3 more Smart Citations